2019
DOI: 10.1186/s12870-019-1834-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation of the ZF-HD gene family in Tartary buckwheat (Fagopyrum tataricum)

Abstract: Background ZF-HD is a family of genes that play an important role in plant growth, development, some studies have found that after overexpression AtZHD1 in Arabidopsis thaliana , florescence advance, the seeds get bigger and the life span of seeds is prolonged, moreover, ZF-HD genes are also participate in responding to adversity stress. The whole genome of the ZF-HD gene family has been stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 43 publications
8
20
0
1
Order By: Relevance
“…The phylogenetic tree was constructed with TaZF-HD, AtZF-HD and OsZF-HD proteins ( Table S2 ). The results indicated that TaZF-HD proteins were divided into six groups ( Figure 1 and Figure 2 A), which were consistent with previous phylogenetic analyses of plant ZF-HD proteins [ 16 , 18 ]. Group II and MIF were the largest with 10 and 9 members, respectively.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The phylogenetic tree was constructed with TaZF-HD, AtZF-HD and OsZF-HD proteins ( Table S2 ). The results indicated that TaZF-HD proteins were divided into six groups ( Figure 1 and Figure 2 A), which were consistent with previous phylogenetic analyses of plant ZF-HD proteins [ 16 , 18 ]. Group II and MIF were the largest with 10 and 9 members, respectively.…”
Section: Resultssupporting
confidence: 90%
“…In this study, we identified 37 TaZF-HD genes in wheat including 28 TaZF-HD genes and nine TaMIF genes ( Figure 1 and Table S1 ). The number of TaZF-HD genes was relatively higher than that identified in Arabidopsis (17) [ 11 ], tomato (22) [ 16 ], Chinese cabbage (31) [ 12 ] and Tartary buckwheat (20) [ 18 ] and the same as that in cotton (37) [ 17 ], suggesting that genome duplication events might have contributed to the expansion of TaZF-HD genes in wheat. Thirty-six paralogous gene pairs were identified in wheat, which all had undergone WGD or segmental duplication events and a strong purifying selection pressure ( Figure 4 and Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tartary buckwheat is a dicotyledonous plant in the Polygonaceae family that contains a variety of nutrients, especially flavonoids such as rutin and quercetin [26]. Until now, transcription factor families such as ARF, MADS, AP2/ ERF, NAC, bZIP, ZF-HD have been identified in Tartary buckwheat [2732]. More importantly, through in-depth research of ARF2 , it has been found that ARF2 plays an important role in determining the final size of Tartary buckwheat fruit [33].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analyses showed that ZF-HD proteins were divided into two subfamilies, ZHD and MIF (Mini Zinc nger), and MIF genes only possess zinc nger structure but lacking HD domains at C-terminal, which similar with ZHD proteins without introns [6]. Since the rst ZF-HD TF was identi ed in the C4 plant Flaveria bidentis [7], a series of studies in plants have focused on ZF-HD TFs, including Arabidopsis thaliana [8], Oryza sativa L. [9], Solanum lycopersicum [10], Fagopyrum tataricum [11] and Glycine max [12]. ZF-HD genes play pivotal roles including the regulation of plant growth and development, hormone conduction and various environmental stresses [12,13].…”
Section: Introductionmentioning
confidence: 99%